2005
DOI: 10.1002/ptr.1769
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant properties of germinated fenugreek seeds

Abstract: Fenugreek (Trigonella foenum-graecum) is used as a spice, vegetable and a medicinal plant. Since antioxidant properties have been linked to health benefits of natural products, such properties were studied in germinated fenugreek seeds which are considered to be more beneficial than dried seeds. Different fractions of the germinated seeds were used to determine their antioxidant potential at different levels. The assays employed were ferric reducing antioxidant power, radical scavenging by 1,1-diphenyl-2-picry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
105
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 190 publications
(121 citation statements)
references
References 22 publications
8
105
0
1
Order By: Relevance
“…The positive effect of parsley extract on high density lipoprotein seemed to be in agreement with the results of Abd El-Baky (2011) and Baghdadi (2014). Our results indicated that inclusion of parsley in the diet caused an increase in the total antioxidant capacity, and these outcomes were in line with the results reported by (Nielsen et al, 1999;Rajeshwari et al, 2011a,b;Dixit et al, 2005). Reactive oxygen species concentrations increase with age, concomitantly with decreases in antioxidant levels (Weir and Robaire 2007;Vazquez-Memije et al, 2008).…”
Section: Blood Compoundssupporting
confidence: 92%
“…The positive effect of parsley extract on high density lipoprotein seemed to be in agreement with the results of Abd El-Baky (2011) and Baghdadi (2014). Our results indicated that inclusion of parsley in the diet caused an increase in the total antioxidant capacity, and these outcomes were in line with the results reported by (Nielsen et al, 1999;Rajeshwari et al, 2011a,b;Dixit et al, 2005). Reactive oxygen species concentrations increase with age, concomitantly with decreases in antioxidant levels (Weir and Robaire 2007;Vazquez-Memije et al, 2008).…”
Section: Blood Compoundssupporting
confidence: 92%
“…Fenugreek contains phenolic and flavonoids compounds which help to enhance its antioxidants capacity [11]. It also have an ability to lower the hepatic lipids in body because of its potential to modify the activities of several enzymes such as enzymes related to glucose and lipid metabolism [12].…”
Section: Introductionmentioning
confidence: 99%
“…It has been stated that fenugreek seed extract reduces lipid peroxidation and hemolysis in RBC (53). Dixit et al 2005 have shown that the aqueous fraction of fenugreek exhibit higher antioxidant activity compared with other fractions (54). Fenugreek extract scavenges hydroxyl radicals and inhibits H 2 O 2 -induced lipid peroxidation in rat liver mitochondria (55).…”
Section: Anticarcinogenic Effect and Antioxidant Activitymentioning
confidence: 99%